The Effect of Compost Fertilizer on the Quality of Tangerine of the Batu 55 Variety (Citrus reticulata Blanco) - Jefrisko Alfredo; Julianus Jeksen; Henderikus Darwin Beja (ITScience (Information Technology and Science), 2026)
This study aimed to compare the quality of Batu 55 tangerine (Citrus reticulata Blanco) fruit cultivated at PT. Kusuma Satria Dinasari Wisatajaya (Kusuma Agrowisata), Batu City, East Java, with the quality description of the national superior variety as stipulated in the Decree of the Minister of Agriculture No. 307/Kpts/SR.120/4/2006. The research was conducted for approximately four months, from September to November 2025, using a comparative research approach. Plant sampling was carried out using a systematic sampling method, involving 23 sample trees selected from a total population of 150 trees in Block A2. The observed variables included the number of fruits per tree, fruit diameter, fruit weight per fruit, and fruit sweetness level (% Brix). Compost fertilizer was applied at a dosage of 30 kg per tree as the cultivation treatment. The collected data were analyzed comparatively by contrasting field observation results with the official quality standards of the Batu 55 tangerine variety. The results indicated that compost application improved several physical quality attributes of Batu 55 tangerine fruit, particularly the number of fruits per tree, fruit diameter, and fruit weight, while the fruit sweetness level did not reach the standard value. Overall, the fruit quality generally met the characteristics of the superior variety, although variations were influenced by environmental conditions and cultivation practices. This study provides useful information for evaluating fruit quality and supporting sustainable cultivation of Batu 55 tangerines.